2009
DOI: 10.1075/pbns.182.09ker
|View full text |Cite
|
Sign up to set email alerts
|

Humor and interlanguage in a bilingual elementary school setting

Abstract: This article focuses on the relationship between humor and language acquisition in a bilingual immersion setting. Data stems from picture story narrations by 18 informants taking part in an English immersion program in Germany. The analysis concentrates on instances of laughter and smiling as they appear spontaneously during the child narrations. In an initial step, different categories of laughter are identified and subsequently analyzed with regard to their relation to humor and to (the second) language, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…New developments in the CA‐inspired SLA research that have emerged and proliferated in the past decade or so (e.g., Mori & Markee, ) have opened up an exciting arena for the detailed analysis of interactions that involve laughter (but not necessarily humor per se; see, e.g., Bushnell, ; Sert & Jacknick, ; Waring, ). These studies often reported on the instances of laughter produced in the face of interactional troubles or linguistic inadequacy (Kersten, ; Ohta, ; Petitjean & González–Martínez, ; Sert & Jacknick, ). Laughter in troubled situations was found to play various roles, such as indicating the presence of troubles, mitigating the seriousness of troubles, and even preempting and solving the troubles.…”
Section: Introductionmentioning
confidence: 99%
“…New developments in the CA‐inspired SLA research that have emerged and proliferated in the past decade or so (e.g., Mori & Markee, ) have opened up an exciting arena for the detailed analysis of interactions that involve laughter (but not necessarily humor per se; see, e.g., Bushnell, ; Sert & Jacknick, ; Waring, ). These studies often reported on the instances of laughter produced in the face of interactional troubles or linguistic inadequacy (Kersten, ; Ohta, ; Petitjean & González–Martínez, ; Sert & Jacknick, ). Laughter in troubled situations was found to play various roles, such as indicating the presence of troubles, mitigating the seriousness of troubles, and even preempting and solving the troubles.…”
Section: Introductionmentioning
confidence: 99%
“…Dynel 2016;Chovanec 2012), school settings (e.g. Kersten 2009;Schnurr et al 2016), and sports teams (e.g. Wolfers et al 2017;Hester 2010).…”
Section: Introductionmentioning
confidence: 99%